Development of a prototype vegetable and fruit semi-automatic slicer machine / Muhammad Aimanfikri Md Rizal and Norhisyam Jenal - Md Rizal, Muhammad Aimanfikri; Jenal, Norhisyam (School of Mechanical Engineering, 2023)
Vegetables must be manually cut and sliced, which takes a lot of time and increases the chance that the food may become contaminated, increasing the danger of contracting foodborne illnesses. Vegetables have been reduced in size using a variety of techniques, including manual, electric, and automated ones. To save time and energy, this project attempts to create a mechanized vegetable slicer. The major goal of the entire project was to create a design that is quick, simple, relatively inexpensive, and effective when reducing the size of vegetables. As a direct current motor powers this automatic vegetable slicer because it is more effective and energy-saving, cutting vegetables can be done more quickly. In conclusion, this automated vegetable slicer will be helpful to busy and lower-income families or university students for the cheapest price.